SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) BERBASIS WEB MOBILE - Yulianton, Heribertus; Nugrahaeni, Pipit Fitriana (Information Technology and Telematics, 2019)
Abstract Acceptance of new employees is important for a company to occupy available positions. In some companies still use the usual methods in the environment such as friendship processes, or family relationships. After work, it turns out that employees do not have the skills or criteria that are suitable for the company. Therefore, the HRD (Human Resource Department) must have information and must be selective about applicants entering the company. The method used for the new employee acceptance decision support system uses the Simple Additive Weighting (SAW) method. Making programs using PHP and MySQL databases. The results of the system supporting new employee recruitment decisions are in the form of assessments that will select the best alternative from a number of alternatives based on rankings. In this case the intended alternative is a new prospective employee who has the best value based on the employee acceptance criteria.